Stirred Milling-New Comminution Technology In The PGM Industry - Synopsis - C. M. Rule (The Southern African Institute of Mining and Metallurgy, 2011)
Stirred milling using either horizontal or vertical mills has made a rapid entrance into PGM ore and tailings concentrator flow sheets. Currently there are in excess of 40 units installed in either mainstream, ?MIG? or intermediate concentrate regrind, ?UFG?, applications in PGM, primary ore treatment plants or in tailings scavenging and reclamation treatment plants. This represents a total of approximately 70 MW of installed fine grinding equipment. This paper outlines the reasons why the technology take-up has been rapid and illustrates the advantages of this technology over conventional milling. Keywords PGM, platinum group metals, UG2, Merensky, platreef, stirred milling, MIG?mainstream inert grinding, UFG?ultra fine grindingof intermediate flotation concentrates, IsaMill?, Metso SMD?, Deswik, ceremic grinding media, QEMSEM, MLA.